Numerical investigation of droplet-droplet collisions in a water and milk spray with coupled heat and mass transfer. Issue 12 (17th August 2020) - Finotello, Giulia; Padding, Johan T.; Buist, Kay A.; Schijve, Annelien; Jongsma, Alfred; Innings, Fredrik; Kuipers, J. A. M.
Abstract: Large scale simulation models can aid in improving the design of spray dryers. In this work an Eulerian-Lagrangian model with coupled gas phase and droplet heat and mass transfer balances is used to study airflow dynamics, temperature and humidity profiles at different positions in the spray. The turbulent gas flow is solved using large eddy simulation (LES). A turbulent dispersion model accounts for the stochastic subgrid fluid velocity fluctuations along the droplet trajectory. The dispersed phase is treated with Lagrangian transport of droplets, and collisions between droplets which are detected with a stochastic Direct Simulation Monte Carlo (DSMC) method. The outcome of a binary collision is described by collision boundary models for water and milk concentrates. The drying of droplets is modeled by the reaction engineering approach (REA). The effect of the inlet air conditions and of droplet viscosity on the temperature and humidity distributions are analyzed. Most of the heat and mass transfer occurs in the first 10-20 cm from the nozzle where the slip velocities and temperature and humidity driving forces are higher. The droplets size increases, both in the axial and radial direction, because of the dominance of coalescence over separation in the droplet spray studied here. Because the spray domain considered in this work is relatively small, the droplet residence time is small, and consequently the amount of evaporation is still low. The droplet size distributions of milk concentrates are affected by the predominance of coalescence over separation events. The coalescence dominated regime increases when the droplet viscosity is higher.